Diagnostic Accuracy of Galectin‐3 for Well‐Differentiated Thyroid Cancer on Fine‐Needle Aspiration: A Meta‐analysis. (2nd September 2014) - Scheffler, Patrick; Forest, Veronique‐Isabelle; Rochon, Louise; Tamilia, Michael; Mlynarek, Alex M.; Hier, Michael P.; Payne, Richard J.
Abstract : Objectives: (1) Examine and meta‐analyze the literature on galectin‐3 staining on fine‐needle aspiration (FNA) samples of thyroid nodules. (2) Summarize the diagnostic test accuracy of galectin‐3 staining on FNA for well‐differentiated thyroid cancer (WDTC). Methods: A systematic review of studies from 1990 to 2014 examining the diagnostic test properties of galectin‐3 on thyroid nodule samples obtained by FNA with regard to WDTC. Data were meta‐analyzed using DerSimonian‐Laird random effect models for data pooling. Studies were weighted by inverse variance, and between‐study variance was estimated using the Empirical Bayes method. Study heterogeneity and threshold effects were analyzed using the Cochrane Q and Spearman correlation coefficient, respectively. Results: Sixteen studies with 2076 cases were identified. The pooled sensitivity of galectin‐3 for WDTC was 89.4% [confidence interval (CI): 87.2‐91.4], and specificity was 91.9% (CI: 90.2‐93.4). The positive likelihood ratio was 10.05 (CI: 8.24‐12.26), and negative likelihood ratio was 0.12 (CI: 0.10‐0.15). The diagnostic odds ratio of a positive galectin‐3 stain on FNA was 71.3 (CI: 52.7‐96.5). The area under the curve for the summary receiver operating characteristics curve (SROC) was 95.3% (standard error: 0.5%). Conclusions: The current study shows galectin‐3 staining of preoperative thyroid nodule FNA samples to be a test with strong diagnostic accuracy for WDTC, as seen by its favorable sensitivity, specificity, diagnostic odds ratio, and SROC curve. This supports its role as a useful adjunct in the preoperative workup of thyroid nodules.